(untitled) (Eurasian Medical Research Periodical, 2022)
Personal psychological and socio-demographic factors premorbid or background psychopathological symptoms of the development of alcoholism in men and women reflect an important clinical feature. There is insufficient data on the clinical and dynamic aspects of pathology, taking into account the age and sex factors of alcoholism. The aim of the study was to investigate the gender clinical and dynamic characteristics of Alcohol Dependence in adults aged 25 years and over 60 years. For materials and methods clinical-anamnetic, clinical-psychopathological and clinical-dynamic examination of male and female patients treated in Samarkand regional Narcological hospitals and registered in dispensary was conducted. 4 observation groups were divided taking into account gender and age factors. In conclusion, the study made it possible to determine whether the dynamics of alcohol dependence formation in young and late-aged people had gender differences and general age characteristics. The formation of alcoholism in young and late-aged men is characterized by a low and moderate development of the disease and relatively preserved socio-psychological and family ties. The formation of Alcohol Dependence in women of this age group is dangerous and progressive, mainly with a violation of the socio-psychological and family background.